Bioinspired cellulose‐integrated MXene‐based hydrogels for multifunctional sensing and electromagnetic interference shielding. Issue 4 (28th April 2022) - Wei, Jingjiang; Zhu, Chenglong; Zeng, Zhihui; Pan, Fei; Wan, Fuqiang; Lei, Liwen; Nyström, Gustav; Fu, Zhengyi
Abstract: Bioinspired hydrogels are complex materials with distinctive properties comparable to biological tissues. Their exceptional sensitivity to various external stimuli leads to substantial application potential in wearable smart devices. However, these multifaceted hydrogels are often challenging to be combined with pattern customization, stimulus responsiveness, self‐healing, and biocompatibility. Herein, inspired by mussel secretions, a printable, self‐healing, and biocompatible MXene‐based composite hydrogel was designed and prepared by incorporating Ti3 C2 T x MXene nanosheets into the hydrogel framework through the chelation of calcium ions (Ca 2+ ) with polyacrylic acid and cellulose nanofibers at alkaline conditions. The biocompatible conductive hydrogel exhibited sensitivity (gauge factor of 2.16), self‐healing (within 1 s), recognition, and adhesion, distinguishing it as an ideal candidate for wearable multifunctional sensors toward strain sensing, vocal sensing, signature detection, and Morse code transmission. Additionally, the multifunctional hydrogel manifested efficient electromagnetic interference shielding properties (reaching more than 30 dB at a thickness of 2.0 mm), protecting electronics and humans from electromagnetic radiation and pollution. Therefore, the presented work represents a versatile strategy for developing environmentally friendly conductive hydrogels, demonstrating the perspectives of intelligent hydrogels for multifunctional applications. Abstract : Inspired by mussel secretions, a stretchable, adhesive, printable, self‐healing, biodegradable, and the conductive hydrogel is prepared, which can be applied as a strain sensor, a voice sensor, a signature sensor, and a Morse code transmitter concurrently, and act as an electromagnetic interference shielding device to protect the wearable electronics and human body from electromagnetic radiation.